Effect of Diabetes Self-Management Education on Knowledge and HbA1c Levels among Patients with Type 2 Diabetes Mellitus in Occupational Health Care - Margarita, Susan; Arya, Insi Farisa Desy; Mariani, Helni; Setiawati, Elsa Pudji; Kusumawati, Maya; Mutyara, Kuswandewi (Althea Medical Journal, 2025)
Background: Diabetes Self-Management Education (DSME) is a structured self-care program for managing type 2 diabetes mellitus (T2DM), including treatment adherence and complications prevention. This study aimed to evaluate the effect of DSME on diabetes-related knowledge and hemoglobin A1c (HbA1C) levels among patients with T2DM.  Methods: A quasi-experimental pretest-posttest non-equivalent control group design was conducted from August 2023 to January 2024, involving 65 patients with T2DM in occupational health care in Cikarang and Tangerang, Indonesia.  The DSME program included five key components: (1) diabetes mellitus education, (2) medical nutrition therapy, (3) physical exercise, (4) pharmacological intervention; and (5) blood glucose self-monitoring. The intervention group received DSME in six sessions over three weeks (45–60 minutes each), while the control group only reviewed 40 educational slides for 30 minutes. Knowledge was assessed using the Diabetes Knowledge Questionnaire (DKQ-24), and HbA1c levels were measured twice, six months apart. Data were analyzed using independent t-tests, dependent t-tests, and ANOVA. Results: The intervention group (n=26) and control group (n=39) had similar baseline characteristics. A significant improvement in diabetes knowledge was observed in both groups. Interestingly, only the intervention group showed a notable reduction in HbA1c levels (−1.9%), from 8.5% to 6.6%. Post-intervention HbA1c levels differed significantly between groups (p<0.05), with the control group remaining at 8.2%.Conclusions: The DSME program effectively improves knowledge and reduces HbA1c levels in patients with T2DM. It is recommended for integration into occupational health care settings to promote healthy lifestyles and enhance diabetes management.